Utilization of Vegetation Indices to Interpret the Possibility of Oil and Gas Microseepages at Ground Surface. (April 2018) - Susantoro, T M; Wikantika, K; Saepuloh, A; Harsolumakso, A H
Abstract: Microseepages is one way to identify the existence of oil and gas below the surface of the earth. Identification of microseepages could be done using remote sensing approaches. One of the remote sensing data that can be used is Landsat 8. The purpose of this study is to map the potential of microseepages on the ground surface of West Tugu oil and gas field, North West Java Basin, Indonesia. The Landsat 8 data processing were performed including radiometric and geometric corrections, and vegetation indices calculation. The vegetation indices calculated in this study are Normalized Differences Vegetation Index (NDVI), Enhanced Normalized Differences Vegetation Index (ENDVI) and Leaf Area Index (LAI). Based on the vegetation indices, we detected that physical condition of vegetation anomaly served as microseepages location. The results showed that microseepages is identified in the south to the east of the oil and gas field presented by vegetation anomaly. Field survey confirmed the possibility of microseepages is located at yellowish leaf vegetation, high spectral of the leaf at the visible wavelength and low magnetic susceptibility.